Pregunta
upstudy study bank question image url

\& Find \( f+g, f-g, f g \) and \( \frac{f}{g} \). Determine the domain for each function. \( f(x)=5 x+2, g(x)=x-6 \) \( (f+g)(x)=6 x-4 \) (Simplify your answer.) What is the domain of \( f+g \) ? A. The domain of \( f+g \) is \( (-\infty, \infty) \). The dype your answer in interval notation.) \( f+g \) is \( \} \). (Use a comma to separate answers as needed.) C. The domain of \( f+g \) is \( \varnothing \). \( (f-g)(x)=\square \) (Simplify your answer.)

Ask by George Burns. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( (f+g)(x) = 6x - 4 \) Domain of \( f+g \): \( (-\infty, \infty) \) \( (f-g)(x) = 4x + 8 \) Domain of \( f-g \): \( (-\infty, \infty) \) \( fg(x) = 5x^2 - 28x - 12 \) Domain of \( fg \): \( (-\infty, \infty) \) \( \frac{f}{g}(x) = \frac{5x + 2}{x - 6} \) Domain of \( \frac{f}{g} \): \( (-\infty, 6) \cup (6, \infty) \)

Solución

Let's find the functions \( f + g \), \( f - g \), \( fg \), and \( \frac{f}{g} \), along with their respective domains. Given: \[ f(x) = 5x + 2 \] \[ g(x) = x - 6 \] ### 1. \( (f + g)(x) \) **Calculation:** \[ \begin{align*} (f + g)(x) &= f(x) + g(x) \\ &= (5x + 2) + (x - 6) \\ &= 6x - 4 \end{align*} \] **Domain:** Both \( f(x) \) and \( g(x) \) are linear functions defined for all real numbers. Therefore, their sum is also defined for all real numbers. \[ \text{Domain of } f + g: \quad (-\infty, \infty) \] ### 2. \( (f - g)(x) \) **Calculation:** \[ \begin{align*} (f - g)(x) &= f(x) - g(x) \\ &= (5x + 2) - (x - 6) \\ &= 4x + 8 \end{align*} \] **Domain:** Similar to the sum, both \( f(x) \) and \( g(x) \) are defined for all real numbers. Thus, their difference is also defined for all real numbers. \[ \text{Domain of } f - g: \quad (-\infty, \infty) \] ### 3. \( (fg)(x) \) **Calculation:** \[ \begin{align*} (fg)(x) &= f(x) \cdot g(x) \\ &= (5x + 2)(x - 6) \\ &= 5x^2 - 30x + 2x - 12 \\ &= 5x^2 - 28x - 12 \end{align*} \] **Domain:** Since \( f(x) \) and \( g(x) \) are polynomials, their product is also a polynomial and is defined for all real numbers. \[ \text{Domain of } fg: \quad (-\infty, \infty) \] ### 4. \( \left(\frac{f}{g}\right)(x) \) **Calculation:** \[ \left(\frac{f}{g}\right)(x) = \frac{5x + 2}{x - 6} \] **Domain:** The function \( \frac{f}{g} \) is defined for all real numbers except where the denominator is zero. Set the denominator equal to zero and solve for \( x \): \[ x - 6 = 0 \quad \Rightarrow \quad x = 6 \] Therefore, the domain excludes \( x = 6 \). \[ \text{Domain of } \frac{f}{g}: \quad (-\infty, 6) \cup (6, \infty) \] --- ### Summary 1. **\( f + g \)** - **Expression:** \( 6x - 4 \) - **Domain:** \( (-\infty, \infty) \) 2. **\( f - g \)** - **Expression:** \( 4x + 8 \) - **Domain:** \( (-\infty, \infty) \) 3. **\( fg \)** - **Expression:** \( 5x^2 - 28x - 12 \) - **Domain:** \( (-\infty, \infty) \) 4. **\( \frac{f}{g} \)** - **Expression:** \( \frac{5x + 2}{x - 6} \) - **Domain:** \( (-\infty, 6) \cup (6, \infty) \)

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

The Deep Dive

To find \( f + g, f - g, f g, \) and \( \frac{f}{g} \): 1. **Addition**: \[ (f + g)(x) = f(x) + g(x) = (5x + 2) + (x - 6) = 6x - 4. \] The domain of \( f + g \) is \( (-\infty, \infty) \). 2. **Subtraction**: \[ (f - g)(x) = f(x) - g(x) = (5x + 2) - (x - 6) = 5x + 2 - x + 6 = 4x + 8. \] Now about the domain of \( f - g \): since both \( f(x) \) and \( g(x) \) are defined for all real numbers, so is \( f - g \). Thus, the domain is also \( (-\infty, \infty) \). 3. **Multiplication**: \[ (f g)(x) = f(x) \cdot g(x) = (5x + 2)(x - 6). \] The domain of \( fg \) remains \( (-\infty, \infty) \). 4. **Division**: \[ \left( \frac{f}{g} \right)(x) = \frac{f(x)}{g(x)} = \frac{5x + 2}{x - 6}. \] For this function, the domain is all real numbers except \( x = 6 \) (where the denominator is zero), so in interval notation: \( (-\infty, 6) \cup (6, \infty) \). To summarize: - \( (f + g)(x) = 6x - 4 \), domain: \( (-\infty, \infty) \) - \( (f - g)(x) = 4x + 8 \), domain: \( (-\infty, \infty) \) - \( (fg)(x) = (5x + 2)(x - 6) \), domain: \( (-\infty, \infty) \) - \( \left( \frac{f}{g} \right)(x) = \frac{5x + 2}{x - 6} \), domain: \( (-\infty, 6) \cup (6, \infty) \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad